Keloid risk in patients with atopic dermatitis: a nationwide retrospective cohort study in Taiwan. Issue 7 (18th July 2018) - Lu, Ying-Yi; Lu, Chun-Ching; Yu, Wei-Wen; Zhang, Li; Wang, Qing-Rui; Zhang, Cong-Liang; Wu, Chieh-Hsin
Abstract : Objective: The pathogenesis of keloid is largely unknown. Because keloid and atopic dermatitis have overlapping pathophysiological mechanisms, we aimed to evaluate keloid risk in patients with atopic dermatitis. Study design: Population-based retrospective cohort study. Setting: The Taiwan National Health Insurance Research Database was used to analyse data for people who had been diagnosed with atopic dermatitis. Participants: We identified 8371 patients with newly diagnosed atopic dermatitis during 1996–2010. An additional 33 484 controls without atopic dermatitis were randomly identified and frequency matched at a one-to-four ratio. Primary and secondary outcome measure: The association between atopic dermatitis and keloid risk was estimated using Cox proportional hazard regression models. Results: After adjustment for covariates, the atopic dermatitis patients have a 3.19-fold greater risk of developing keloid compared with the non-atopic dermatitis group (3.19vs1.07 per 1000 person-years, respectively). During the study period, 163 patients with atopic dermatitis and 532 patients without atopic dermatitis developed keloid. Notably, keloid risk increased with severity of atopic dermatitis, particularly in patients with moderate to severe atopic dermatitis. Conclusions: Our results indicate that patients with atopic dermatitis had a higher than normal risk of developing keloid and suggest that atopic dermatitis may be an independent risk factor for keloid.